2021
DOI: 10.1007/s40263-021-00867-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cannabidiol on Interictal Epileptiform Activity and Sleep Architecture in Children with Intractable Epilepsy: A Prospective Open-Label Study

Abstract: Background Cannabidiol has been shown to be effective in seizure reduction in patients with Dravet syndrome, Lennox-Gastaut syndrome, and tuberous sclerosis. However, very little is known about its potential to reduce interictal epileptiform activity and improve sleep architecture. Objective The objective of this prospective study was to evaluate the influence of cannabidiol therapy on the frequency of interictal epileptiform discharges (IEDs) and sleep microstructure in a cohort of children with drug-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Positive effects on neuro-cognition were observed in six (20%) patients treated with CBD. There is growing evidence for the improvement of neurocognition and sleep architecture after treatment with CBD [10,15,[19][20][21]. Due to the nature of real-world study data with a small population and the nature of LGS, which is usually accompanied by intellectual disabilities, the neuro-cognitive improvements in our study could not be objectively evaluated using a neuropsychiatric assessment tool, and the main resources for the cognitive and behavioral improvements were caregivers' subjective documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects on neuro-cognition were observed in six (20%) patients treated with CBD. There is growing evidence for the improvement of neurocognition and sleep architecture after treatment with CBD [10,15,[19][20][21]. Due to the nature of real-world study data with a small population and the nature of LGS, which is usually accompanied by intellectual disabilities, the neuro-cognitive improvements in our study could not be objectively evaluated using a neuropsychiatric assessment tool, and the main resources for the cognitive and behavioral improvements were caregivers' subjective documentation.…”
Section: Discussionmentioning
confidence: 99%
“…In-line with this, a recent meta-analysis of CBD trials across multiple therapy areas noted that CBD was only associated with somnolence and sedation in childhood epilepsy trials, most likely owing to interactions with other ASMs such as CLB and VPA [ 94 ]. A small study in children with DRE ( n = 35, including DS, LGS and other genetic epilepsy syndromes) found that of 13 patients with abnormal sleep architecture at baseline, sleep improved in 11 (84.6%) patients [ 95 ].…”
Section: Asms Used In the Treatment Of More Than One Of The Syndromes...mentioning
confidence: 99%
“…They suggest the utility of CBD in reducing IEDs and improving sleep microstructure. Further studies are needed; however, the improvement of behaviour associated with CBD treatment may be due to the reduction in IEDs [35]. This has further implications for studying CBD's effects on cognition.…”
Section: Other Clinical Studiesmentioning
confidence: 99%